Micrographic surgery – four years of experience - Bieniek, Andrzej; Kuniewska, Barbara; Wąsik, Feliks; Cisło, Maria; Włodarczyk, Michał (Contemporary Oncology/Współczesna Onkologia, 1999)
The aim of our investigations was to establish the value of micrographic surgery in the treatment of selected skin neoplasms. Authors introduced the modified Mohs method- according to Breuninger –, based on the full, three dimentional histologic control of the tumour, with emphasis on superficial and deep margins of the specimen, with use of paraffin technique. Material: The cases of Basal Cell Carcinoma (BCC) with higher risk of recurrence, Squamous Cell Carcinoma (SCC), and cancers from skin appendages, stated the basic group of indications. Between 1994 and 1998 in the Wrocław Medical Academy Department of Dermatology, 102 patients (28% of all 364 cancer patients) were treated with use of micrographic surgery. Among those treated, there were 20 patients with primary BCC, 64 with recurrent BCC, 2 with hidradenocarcinoma and 1 with Merkel Cell Carcinoma. The method. The basic margin of resection was between 3 and 15 mm. In case of „positive” margins, the extent of resection was widened in the strictly described points. The reconstruction of the defect was performed as a rule after the full eradication of the tumour, proved by three dimentional histological examinations. The margins of resection were subsequently widened in 52, among 102 treated patients; once in 36 patients, twice in 7, three times in 5, more times in 4 patients. Results: In the follow up period, (between 3 months and 4 years, mean 23 months), the recurrences occured in 4 patients, dissemination of the neoplastic process in next two patients. The obtained results encourage us to the continuation of the procedure.